Protein repeats evolve and emerge in giant viruses - Erdozain Bagolin, Sofía Agostina (2023)
Nucleocytoplasmatic large DNA viruses (NCLDVs or giant viruses) stand out because of their relatively large genomes encoding hundreds of proteins. These species give us an unprecedented opportunity to study the emergence and evolution of repeats in protein sequences. On the one hand, as viruses, these species have a restricted set of functions, which can help us better define the functional landscape of repeats. On the other hand, given the particular use of the genetic machinery of the host, it is worth asking whether this allows the variations of genetic material that lead to repeats in non-viral species. To support research in the characterization of repeat protein evolution and function, we present here an analysis focused on the repeat proteins of giant viruses, namely tandem repeats (TRs), short repeats (SRs), and homorepeats (polyX). Proteins with large and short repeats are not very frequent in non-eukaryotic organisms because of the difficulties that their folding may entail; however, their presence in giant viruses remarks their advantage for performance in the protein environment of the eukaryotic host. The heterogeneous content of these TRs, SRs and polyX in some viruses hints at diverse needs. Comparisons to homologs suggest that the mechanisms that generate these repeats are extensively used by some of these viruses, but also their capacity to adopt genes with repeats. Giant viruses could be very good models for the study of the emergence and evolution of protein repeats.